HIV and Bone Disease: A Perspective of the Role of microRNAs in Bone Biology upon HIV Infection - Fabiola E. Del Carpio-Cano; Raul A. DeLa Cadena; Bassel E. Sawaya (Journal of Osteoporosis)
Increased life expectancy and the need for long-term antiretroviral therapy have brought new challenges to the clinical management of HIV-infected individuals. The prevalence of osteoporosis and fractures is increased in HIV-infected patients; thus optimal strategies for risk management and treatment in this group of patients need to be defined. Prevention of bone loss is an important component of HIV care as the HIV population grows older. Understanding the mechanisms by which HIV infection affects bone biology leading to osteoporosis is crucial to delineate potential adjuvant treatments. This review focuses on HIV-induced osteoporosis within the context of microRNAs (miRNAs) by reviewing first basic concepts of bone biology as well as current knowledge of the role of miRNAs in bone development. Evidence that HIV-associated osteoporosis is in part independent of therapies employed to treat HIV (HAART) is supported by cross-sectional and longitudinal studies and is the focus of this review.